Combined application of melatonin and Bacillus sp. strain IPR-4 ameliorates drought stress tolerance via hormonal, antioxidant, and physiomolecular signaling in soybean - Peter, Odongkara; Imran, Muhammad; Shaffique, Shifa; Kang, Sang-Mo; Rolly, Nkulu Kabange; Felistus, Chebitok; Bilal, Saqib; Dan-Dan, Zhao; Injamum-Ul-Hoque, Md.; Kwon, Eun-Hae; Mong, Mohammad Nazree; Gam, Ho-Jun; et al. (Frontiers in Plant Science, 2024)
The role of melatonin and plant growth-promoting rhizobacteria (PGPR) in enhancing abiotic stress tolerance has been widely investigated. However, mechanism underlying interaction between melatonin and PGPR in drought stress tolerance is poorly understood. In this study, we investigated role of Bacillus sp. strain IPR-4 co-inoculated with melatonin (IPR-4/MET) to ameliorate drought stress response in soybean. Initially, Bacillus sp. strain IPR-4 was isolated from soil samples and validated using 16S rRNA sequencing. At first, survival rate of isolate IPR-4 was assessed in vitro under polyethylene glycol, (5%, 10%, and 15%). Isolate IPR-4 exhibited high survival rate in 15% PEG compared to other isolates. In addition, IPR-4 produced high levels of indole-3-acetic acid and organic acids, coupled with exopolysaccharide, siderophores, and phosphate solubilization under drought stress.To further investigate growth-promoting ability of Bacillus sp. IPR-4 and its potential interaction with MET, bacterial inoculum (40 mL of 4.5 x 10 -8 cells/mL) was applied alone or in combination with MET to soybean plants for 5 days. Then, pre-inoculated soybean plants were subjected to drought stress conditions for 9 days by withholding water under greenhouse conditions. Furthermore, when IPR-4/MET was applied to drought stress plants, significant increase in plant height (33.3%) and biomass fresh weight observed. Similarly, total chlorophyll content increased by 37.1%, whereas activity of peroxidase, catalase, ascorbate peroxidase, superoxide dismutase, and glutathione reductase increased by 38.4%, 34.14%, 76.8%, 69.8%, and 31.6%, respectively. Moreover, hydrogen peroxide content decreased by 37.3%, whereas a reduction of approximately 30% in malondialdehyde was recorded in drought-stressed plants. Regarding the 2,2-diphenyl-1-picrylhydrazyl activity and total phenolic content, an increase of 38% and 49.6%, respectively, was observed. Likewise, Bacillus-melatonin-treated plants enhanced uptake of magnesium, calcium, and potassium by 31.2%, 50.7%, 30.5%, respectively. Under same conditions, salicylic acid content increased by 29.1%, whereas a decreasing abscisic acid content (25.5%) was observed. The expression levels of GmNCED3, GmDREB2, and GmbZIP1 were lowest. However, Bacillus-melatonintreated plants recorded highest expression levels (upregulated) of GmCYP707A1, GmCYP707A2, GmPAL2.1, and GmERD1 in response to drought stress. In a nutshell, these data confirms that Bacillus sp.melatonin co-inoculation has highest plant growth-promoting efficiency under both normal and drought stress conditions.